A note on "Lattice soliton equation hierarchy and associated properties"*Project supported by the Natural Science Foundation of Shandong Province of China (Grant No. ZR2014AM001). (January 2019) - Xu 徐, Xi-Xiang 西祥; Guo 郭, Min 敏
Abstract : We demonstrate that the new hierarchy of integrable lattice equations in Chin. Phys. B 21 090202 (2012) can be changed into the integrable lattice hierarchy in Chin. Phys. B 13 1009 (2004) by using a very simple transformation.